Research advances in intelligent collision avoidance and adaptive cruise control. - Vahidi, A.
This paper looks into recent developments and research trends in collision avoidance/warning systems and automation of vehicle longitudinal/lateral control tasks. It is an attempt to provide a bigger picture of the very diverse, detailed and highly multidisciplinary research in this area. Based on diversely selected research, this paper explains the initiatives for automation in different levels of transportation system with a specific emphasis on the vehicle-level automation. Human factor studies and legal issues are analyzed as well as control algorithms. Drivers' comfort and well being, increased safety, and increased highway capacity are among the most important initiatives counted for automation. However, sometimes these are contradictory requirements. Relying on an analytical survey of the published research, we will try to provide a more clear understanding of the impact of automation/warning systems on each of the above-mentioned factors. The discussion of sensory issues requires a dedicated paper due to its broad range and is not addressed in this paper.
Keywords: Adaptive cruise control; Collision warning; Driver comfort; Highway capacity; Human factor studies; Intelligent collision avoidance; Multidisciplinary research; Transportation system automation; Vehicle lateral control tasks; Vehicle longitudinal control tasks; Vehicle-level automation; Warning systems